(3GdUGOM hGdHGZes - (3eMeO Hf eMeO Hf UGdM GdYHGSj, fXGe GdOjf CHh jYdj, GHf GdgHGQjI , J (B509 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi MHGfi HGdCUZQjf GdbdH hGddSGf gPG cJGH ajg Yde hCOH jahb CfhGY GdbQjV hGdNWH s
(3BNQgG (B:s
(3GdaNGQ hGdYdG EQfc ef Ohf GdedG Je cJGH GdUGOM hGdHGZe hGdMGRe hGdeYGRe s
(3efXheI Ydi ESdhH cdjdI hOefI ai Cdai HjJs
(3YdjgG JedcGJ CbOegG SfI (B924 (3g`s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1069s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs